MTA1 Promotes Hepatocellular Carcinoma Progression by Downregulation of DNA-PK-Mediated H1.2T146 Phosphorylation - Li, Yu-Hui; Zhong, Ming; Zang, Hong-Liang; Tian, Xiao-Feng (Frontiers in Oncology, 2020)
Global incidence and mortality associated with hepatocellular carcinoma (HCC) is steadily increasing. Metastasis-Associated 1 (MTA1) can induce tumorigenesis and metastatic progression in HCC. However, the mechanistic details of MTA1-mediated regulation of HCC has not been completely defined. Epigenetic histone modification is closely related to tumor development. Histone cluster 1 H1 family member c (H1.2) is important for epigenetic histone modification and chromatin remodeling; however if it has a role in HCC tumorigenesis is not knows. In the current study, we confirmed that MTA1 promoted HCC cell growth and migration. Our results further show that MTA1 inhibited the phosphorylation of histone cluster 1 H1 family member c (H1.2) at threonine-146 residue (T146) (H1.2T146ph). MTA1 inhibited H1.2T146ph by mediating proteasomal degradation of the DNA protein kinase (DNA-PK). Pharmacological inhibition of proteasomal degradation of DNA-PK or genetic ablation of E3 ligase MDM2 rescued expression of DNA-PK and subsequent phosphorylation of H1.2. MTA1’s role in HCC was inhibited by ectopic expression of H1.2T146ph in HCC cell lines. Our results showed that H1.2T146ph can bind to MTA1 target genes. Collectively, our study confirms that MTA1 functions as an oncogene and promotes HCC progression. The epigenetic histone modifier H1.2T146ph exerts critical role in regulation of MTA1-induced tumorigenesis. MTA1 regulates post-translational activation of H1.2 by regulating the cognate kinase, DNA-PK, via the ubiquitin proteasome system. MTA1 expression was inversely correlated to both DNA-PK and phosphorylated H1.2 in HCC tissue specimens compared to tumor adjacent normal hepatic tissue, revealing that the MTA1/MDM2/DNA-PK/H1.2 as an important therapeutic axis in HCC.